A Systematic Review of the Evidence for Impaired Cognitive Theory of Mind in Maltreated Children - Benarous, Xavier; Guilé, Jean-Marc; Consoli, Angèle; Cohen, David (Frontiers in Psychiatry, 2015)
Compared to the large number of studies exploring difficulties in emotion recognition in maltreated children, few (N=12) have explored the cognitive aspect of theory of mind, i.e., the ability to understand others’ thoughts and intentions. A systematic review of these studies shows inconsistent results regarding cognitive theory of mind tasks. Youths with a history of maltreatment are more likely to fail at false belief tasks (N=2). However, results are less conclusive regarding other tasks (perspective-taking tasks, N=4; and hostile attribution tasks, N=7). Additionally, only one study controlled for potential psychopathology. Measures of psychopathology and other cognitive abilities, in addition to theory of mind, are required to establish a specific association between maltreatment and the cognitive dimension of theory of mind.